Multi objective load frequency control using hybrid bacterial foraging and particle swarm optimized PI controller. (July 2016) - Dhillon, Sukhwinder Singh; Lather, J.S.; Marwaha, S.
Highlights: A hybrid approach based on BFOA and PSO algorithm for control design is proposed. The proposed control design has been implemented on three area power system. The results have been shown to provide better results over the existing ones. Robustness analysis of the proposed technique is carried out. Abstract: Excessive load demand with reliability in power availability, demands for interconnection of large number of generating units over existing tie lines. Due to sudden change in demand, the power transfer over existing tie lines working close to their thermal limits results in low frequency power oscillations. Thus, in modern power systems the study of mitigation of these frequency oscillations is more involved and formulates the area of Load Frequency Control (LFC). Many conventional and heuristic control techniques have been recently applied to address the issue of LFC. This paper investigates load frequency control of large interconnected power system consisting of conventional and renewable energy sources, using hybrid heuristic approach. The proposed strategy is shown to result in improved system damping resulting in faster mitigation of low frequency oscillations.